Pengaruh Teknik Relaksasi Nafas Dalam Terhadap Penurunan Nyeri Persalinan Kala I Fase Aktif Di Bpm Wulan Kelurahan Muara Kelingi Kabupaten Musi Rawas - Annisa, Kintan; Umami, Desi Aulia; Ernani, Ernani (Jurnal Multidisiplin Dehasen (MUDE), 2025)
Childbirth is the process of movement of the fetus, placenta and membranes from the uterus through the birth canal. Most (90%) labor is accompanied by pain. In the active phase, there is an increase in the intensity and frequency of contractions, resulting in a peak pain response. Labor pain can cause various physiological and psychological changes in the mother. This study aims to determine the effect of deep breathing relaxation techniques on reducing labor pain during the first active phase. The type of design in this research is pre-experimental with one group pretest-posttest design. The total sample was 30 respondents. The sampling technique uses the total sampling method. Data collection techniques used questionnaire sheets and the Numeric Rating Scale (NRS) pain scale. Data analysis used paired T test. The results of the study showed that the pain intensity of respondents in the group before being given treatment was an average of 7.00 and after being given treatment an average of 5.47. The results of data analysis obtained a significance value of ρ = 0.000 (ρ <0.05). In conclusion, there is an effect of providing deep breathing relaxation techniques on reducing labor pain during the first active phase.